Supramolecular approaches to engineering cell signalling networks in artificial cells - Gartland, SA (2024)
This thesis describes the design and synthesis of artificial cell signalling networks in artificial cells. By appending a photo-removable protecting group to hydroxyquinoline clioquinol, the pro-transporter can be anchored to an artificial phospholipid bilayer and selectively released by photo irradiation. The implementation of this system for Zn(II) activated aqueous phase catalysis is then attempted. Chapter 1 establishes the field of transmembrane ion transport, including discussion into the biological relevance of phospholipid membranes and highlights key examples of synthetic biomimetic ion transporters, including stimulus responsive systems. Chapter 2 introduces clioquinol and describes its properties as a transmembrane Zn(II) transporter. The design and synthesis of photo-caged clioquinol for light-responsive cation coordination and transport is then discussed. Chapter 3 describes the use of photo-caged clioquinol as messengers in stimulus responsive cell signalling networks, beginning with un-modified photo-responsive systems and moving on to demonstrate increased anchoring efficiency by the implementation of hydrophobic anchoring groups. Chapter 4 expands on the signalling networks established in chapter 3 by introducing a novel watersoluble pyridyl dioxime, capable of aqueous phase catalysis upon Zn(II) coordination. Chapter 5 outlines the experimental procedures employed in these works.